Metabolomic Study of Normal and Modified Nucleosides in the Urine of Mice with Lipopolysaccharide‐Induced Sepsis by LC–MS/MS. (14th February 2021) - Ji, Moongi; Lee, Hyeon‐Seong; Kim, Youngbae; Seo, Chan; Oh, Songjin; Jung, In Duk; Park, Jae‐Hyun; Paik, Man‐Jeong
Abstract : Endogenous normal and modified nucleosides have been studied as potential biomarkers of various inflammatory diseases including sepsis. However, no systematic nucleoside profiling and pattern analysis study has been performed in sepsis. In this study, simultaneous liquid chromatography–mass spectrometry profiling of normal and modified nucleosides was performed to characterize altered nucleoside metabolism in sepsis mice. Abstract : The devised method showed good linearity ( r ≥ 0.998) and had detection and quantification limits of 0.0020–0.60 and 0.0060–1.81 pg, respectively. Repeatability, expressed as a percentage of relative standard deviation (% RSD), varied from 0.7 to 4.8, and accuracy, expressed as a percentage of relative error (% RE) ranged from −6.2 to 9.01. When applied to mouse urine samples, four normal and six modified nucleosides were identified. In multivariate analysis, 1‐methylguanosine and inosine were evaluated as potential biomarkers of sepsis, which suggests the devised nucleoside profiling and pattern analyses technique might be useful for monitoring and screening sepsis.